Search for massive resonances decaying into WW, WZ or ZZ bosons in proton-proton collisions at $\sqrt{s} = $ 13 TeV - CMS collaboration (2239 authors) (2017)
A search is presented for new massive resonances decaying to WW, WZ or ZZ bosons in $ \ell ν q\overline{q} $ and $ q\overline{q}q\overline{q} $ final states. Results are based on data corresponding to an integrated luminosity of 2.3-2.7 fb$^{−1}$ recorded in proton-proton collisions at $ \sqrt{s}=13 $ TeV with the CMS detector at the LHC. Decays of spin-1 and spin-2 resonances into two vector bosons are sought in the mass range 0.6-4.0 TeV. No significant excess over the standard model background is observed. Combining the results of the $ \ell ν q\overline{q} $ and $ q\overline{q}q\overline{q} $ final states, cross section and mass exclusion limits are set for models that predict heavy spin-1 and spin-2 resonances. This is the first search for a narrow-width spin-2 resonance at $ \sqrt{s}=13 $ TeV.